Peran Osis dalam Meningkatkan Kepedulian terhadap Lingkungan pada SMP Katolik Lamaholot 1912 Watoone - Scholastika Aloysia Lelan; Indriyati Indriyati; Yohana Fransiska Medho; Yasinta P. Peten; Alfry Sinlae; Karolus Tatu Sius; Hendrikus L. Kaha (Universitas Kristen Indonesia Toraja, 2024)
This work program is aimed at strengthening the role of OSIS in increasing students' awareness of the school environment. Method of implementing the work program with socialization and training in making trash bins made from bamboo plants. This work program aims to identify OSIS strategies in preserving the school environment. The results of implementing the work program show that OSIS can mobilize students through various activities such as waste management, reforestation and environmental education. The benefits of this work program are to increase awareness of the importance of environmental cleanliness and build students' sense of concern for school.